Studi Tentang Mutu Biji Pala Dengan Pengeringan Matahari dan Pengasapan - Rahmadini, Nova; Marzuki, Ilyas; Laimeheriwa, Semuel (Universitas Pattimura, 2023)
The quality of nutmeg seeds is determined, among others, by their moisture content and the presence of aflatoxin contamination. To maintain quality, the moisture content of nutmeg seeds must be reduced to meet export standards. This can be achieved through sun drying or smoking. Aflatoxin is a mycotoxin produced by the Aspergillus fungi. The study aims to obtain nutmeg seeds with the appropriate moisture content according to the Indonesian National Standard (SNI) through sun drying and smoking methods. Also, it is to qualitatively identify the presence of aflatoxin in the nutmeg seeds. A total of 27 kg of nutmeg was divided into three treatment groups for drying and smoking. The drying and smoking treatments were arranged following a Randomized Block Design with three replications. Nutmeg essential oil was extracted using steam distillation. Subsequently, a qualitative identification of aflatoxin contamination was carried out using PDA media. The results showed that sun drying the nutmeg seeds for 72 hours resulted a moisture content of 7 - 8%. Meanwhile, the qualitative identification revealed the presence of Aspergillus niger, Penicillium sp, and Rhizopus stolonifer in the tested samples. No A. flavus, however, which is the main fungus responsible for aflatoxin production, was found in the results. Therefore, by drying the nutmeg seeds to a moisture content below 10%, the emergence of aflatoxin-causing fungi can be prevented.